2010
DOI: 10.1371/journal.pone.0009596
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Potential Distribution of Bacillus anthracis under Multiple Climate Change Scenarios for Kazakhstan

Abstract: Anthrax, caused by the bacterium Bacillus anthracis, is a zoonotic disease that persists throughout much of the world in livestock, wildlife, and secondarily infects humans. This is true across much of Central Asia, and particularly the Steppe region, including Kazakhstan. This study employed the Genetic Algorithm for Rule-set Prediction (GARP) to model the current and future geographic distribution of Bacillus anthracis in Kazakhstan based on the A2 and B2 IPCC SRES climate change scenarios using a 5-variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 66 publications
(109 reference statements)
4
72
0
3
Order By: Relevance
“…If one considers the scarcity of resources, the vaccination strategy should identify target areas for vaccination based on the understanding of the spatial ecology and the geographic distribution of B. anthracis in Bangladesh, as has been done in other settings. 28,29 Because some human cases were reported more than one month after the onset of illness, imperfect recall by the case-patients might be a reason that 24 (9%) of the 273 cutaneous anthrax case-patients did not report a history of any of the exposures related to contact with a sick animal, meat of a sick slaughtered animal, or animal by-products. There might also have been some unknown exposure because the surrounding environment was contaminated by disposed animal carcasses, and stable flies and mosquitoes may play a role in transmission of animal and human anthrax.…”
Section: Discussionmentioning
confidence: 99%
“…If one considers the scarcity of resources, the vaccination strategy should identify target areas for vaccination based on the understanding of the spatial ecology and the geographic distribution of B. anthracis in Bangladesh, as has been done in other settings. 28,29 Because some human cases were reported more than one month after the onset of illness, imperfect recall by the case-patients might be a reason that 24 (9%) of the 273 cutaneous anthrax case-patients did not report a history of any of the exposures related to contact with a sick animal, meat of a sick slaughtered animal, or animal by-products. There might also have been some unknown exposure because the surrounding environment was contaminated by disposed animal carcasses, and stable flies and mosquitoes may play a role in transmission of animal and human anthrax.…”
Section: Discussionmentioning
confidence: 99%
“…These data were obtained from a larger database development effort in collaboration with the Kazakh Science Center for Quarantine and Zoonotic Disease in Almaty, Kazakhstan, described in detail elsewhere (Aikembayev et al, 2010;Joyner et al, 2010;Kracalik et al, 2011). The data were divided into livestock groups based on results of Aikimbayev et al (2010), which suggested that cases within each group where distributed differently. Broadly, this subset of data reflects the time period after mass vaccination was implemented and corresponds to the averaged climate data from the WorldClim data set use in the environmental analysis (see below).…”
Section: Geographical Information Systems (Gis) Database Developmentmentioning
confidence: 99%
“…Recently, GARP rules have been used to build and graph climatic envelopes for a specific genetic sub-lineage of Bacillus anthracis in Kazakhstan, compared to models built from larger data sets representing outbreaks regardless of genotype (Mullins et al 2011). This process also allows the user to project models onto landscapes where occurrence data are unavailable, such as when surveillance or reporting are lacking (Blackburn 2010), or onto the same landscape in future time periods to evaluate the effects of climate change (Holt et al 2009;Blackburn 2010;Joyner et al 2010).…”
mentioning
confidence: 99%